Exploring the Potential Roles of Band 3 and Aquaporin-1 in Blood CO2 Transport–Inspired by Comparative Studies of Glycophorin B-A-B Hybrid Protein GP.Mur - Hsu, Kate (Frontiers in Physiology, 2018)
The Cl-/HCO3- exchanger band 3 is functionally relevant to blood CO2 transport. Band 3 is the most abundant membrane protein in human red blood cells (RBCs). Our understanding of its physiological functions mainly came from clinical cases associated with band 3 mutations. Severe reduction in band 3 expression affects blood HCO3-/CO2 metabolism. What could happen physiologically if band 3 expression is elevated instead? In some areas of Southeast Asia, about 1 - 10% of the populations express GP.Mur, a glycophorin B-A-B hybrid membrane protein important in the field of transfusion medicine. GP.Mur functions to promote band 3 expression, and GP.Mur red cells can be deemed as a naturally-occurred model for higher band 3 expression. This review first compares the functional consequences of band 3 at different levels, and suggests a critical role of band 3 in postnatal CO2 respiration. The second part of the review explores the transport of water, which is the other substrate for intra-erythrocytic CO2/HCO3- conversion (an essential step in blood CO2 transport). Despite that water is considered unlimited physiologically, it is unclear whether water channel aquaporin-1 (AQP1) abundantly expressed in RBCs is functionally involved in CO2 transport. Research in this area is complicated by the fact that the H2O/CO2-transporting function of AQP1 is replaceable by other erythrocyte channels/transporters (e.g. UT-B/GLUT1 for H2O; RhAG for CO2). Recently, using carbonic anhydrase II (CAII)-filled erythrocyte vesicles, AQP1 has been demonstrated to transport water for the CAII-mediated reaction, CO2(g) + H2O ⇌ HCO3-(aq) + H+(aq). AQP1 is structurally associated with some population of band 3 complexes on the erythrocyte membrane in an osmotically-responsive fashion. The current findings reveal transient interaction among components within the band 3-central, CO2-transport metabolon (AQP1, band 3, CAII and deoxygenated hemoglobin). Their dynamic interaction is envisioned to facilitate blood CO2 respiration, in the presence of constantly-changing osmotic and hemodynamic stresses during circulation.